Cost-effectiveness of extending the coverage of water supply fluoridation for the prevention of dental caries in Australia. - Cobiac, L; Vos, T (2012)
OBJECTIVE: Fluoride was first added to the Australian water supply in 1953, and by 2003, 69% of Australia's population was receiving the minimum recommended dose. Extending coverage of fluoridation to all remaining communities of at least 1000 people is a key strategy of Australia's National Oral Health Plan 2004-2013. We evaluate the cost-effectiveness of this strategy from an Australian health sector perspective. METHODS: Health gains from the prevention of caries in the Australian population are modelled over the average 15-year lifespan of a treatment plant. Taking capital and on-going operational costs of fluoridation into account, as well as costs of caries treatment, we determine the dollars per disability-adjusted life years (DALY) averted from extending coverage of fluoridation to all large (≥ 1000 people) and small (<1000 people) communities in Australia. RESULTS: Extending coverage of fluoridation to all communities of at least 1000 people will lead to improved population health (3700 DALYs, 95% uncertainty interval: 2200-5700 DALYs), with a dominant cost-effectiveness ratio and 100% probability of cost-savings. Extending coverage to smaller communities leads to 60% more health gains, but is not cost-effective, with a median cost-effectiveness ratio of A$92 000/DALY and only 10% probability of being under a cost-effectiveness threshold of A$50 000/DALY. CONCLUSIONS: Extension of fluoridation coverage under the National Oral Health Plan is highly recommended, but given the substantial dental health disparities and inequalities in access to dental care that currently exist for more regional and remote communities, there may be good justification for extending coverage to include all Australians, regardless of where they live, despite less favourable cost-effectiveness.